Allegorical Poetics and the Epic : the Renaissance Tradition to Paradise Lost. - Treip, Mindele Anne (Studies in the English Renaissance., 2015)
Literary allegory has deep roots in early reading and interpretation of Scripture and classical epic and myth. In this substantial study, Mindele Treip presents an overview of the history and theory of allegorical exegesis upon Scripture, poetry, and especially the epic from antiquity to the seventeenth and early eighteenth centuries, with close focus on the Renaissance and on the triangular literary relationship of Tasso, Spenser, and Milton. Exploring the different ways in which the term allegory has been understood, Treip finds significant continuities-within-differences in a wide range of.